THE ROLE OF BEHAVIORAL INTENTIONS TO USE MOBILE BANKING: APPLICATION OF THE UTAUT2 METHOD WITH SECURITY, TRUST AND RISK FACTORS - Dwi Pratama, Rico Rivaldi; Renny Renny (Dinasti Publisher, 2022)
The warning for social distancing from the Government during the Covid-19 pandemic has implications for main activities, one of which is conducting financial transactions. Therefore, there is a need for information for the public and mobile banking service providers regarding the dominant factors that influence behavioral intentions and use behavior. This study aims to analyze the role of the behavioral intentions of using mobile banking by applying the Unified theory of acceptance and use of technology 2 (UTAUT2) method combined with security, trust and risk as supporting factors. The data used is the data from the questionnaire. The method used is UTAUT2 with SEM-PLS as a tool to determine the effect of each variable. The results of this study indicate that performance expectancy, effort expectancy, facilitating conditions, habit and trust have a positive effect on behavioral intentions, price values have a negative effect on behavioral intentions and social influences, hedonic motivation, risk and security have no influence on behavioral intentions. In addition, habit and behavioral intention have a positive effect on use behavior, while the facilitating conditions has no influence. Age, gender, and experience can moderate the influence of habits on use behavior and experience can moderate the effect of behavioral intention on use behavior.